Adhesive interlining and clothing fabric equipped with same
By integrating a visible light-responsive photocatalyst into the adhesive interlining's resin, the issue of stain accumulation in clothing products is addressed, resulting in reduced noticeable stains and maintained adhesion performance.
Patent Information
- Application Number
- JP2022530476
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-08
- Filing Date
- 2021-05-31
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2041-05-31
AI Technical Summary
Existing clothing products with adhesive interlinings face noticeable stains over time due to dirt accumulation in the resin adhesive portion, which is not effectively addressed by conventional anti-stain processing methods.
Incorporating a visible light-responsive photocatalyst into the adhesive interlining's resin, which decomposes dirt upon exposure to visible light, preventing its accumulation and maintaining adhesion performance.
The solution effectively suppresses noticeable stains over time by decomposing dirt in the adhesive interlining's resin, while maintaining good adhesion to the outer material.
Smart Images

Figure 0007656208000002 
Figure 0007656208000003 
Figure 0007656208000004
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to an adhesive interlining and a clothing fabric comprising the same. [Background technology]
[0002] There are known techniques for preventing the adhesion of dirt, such as sebum and grime secreted from the human body, which can cause stains on clothing such as shirts and blouses. For example, Patent Document 1 shown below describes a stain-resistant processing method in which a base fabric of an adhesive interlining constituting a collar or cuff part of a shirt or blouse is treated to be water- and oil-repellent, and the part is sewn to the main body of the shirt or blouse. This stain-resistant processing method can prevent the adhesion of the above-mentioned dirt without impairing the inherent properties of the fabric, such as water absorption or texture. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-213509 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, even in clothing using such technology, stains caused by dirt may become noticeable over time. As a result of extensive research, the inventors of the present application have found the cause of the stains that occur over time becoming more noticeable. First, they have found that stains on these clothing are caused by dirt adhering to each of the following areas. (1) Stains on the surface (2) Stains on the base fabric of the adhesive interlining (3) Dirt adhering to the resin adhesive part of the adhesive interlining
[0005] The inventors of the present application have found that stains that develop over time on the collars and other parts of clothing are largely attributable to the above-mentioned type (3) of stain. That is, while the above-mentioned types (1) and (2) of stain are easily removed by washing using the above-mentioned conventional stain-resistant processing methods, no measures have been taken for the above-mentioned type (3) of stain, and the stain could not be removed even by washing. Moreover, they have found that stains accumulate inside the resin that constitutes the resin adhesive part over time, and that the accumulated stains appear as stains.
[0006] Therefore, an object of one aspect of the present invention is to provide an adhesive interlining that can reduce the visibility of stains that occur over time, and a clothing fabric including the adhesive interlining. [Means for solving the problem]
[0007] The adhesive interlining according to one aspect of the present invention comprises a base fabric and adhesive resin parts made of resin and provided in a dot pattern on one surface of the base fabric, the resin having a viscosity of 0.01 g / m 2 ~1.30g / m 2 A visible light responsive photocatalyst is added.
[0008] The visible light responsive photocatalyst referred to here is a catalyst that can exhibit photocatalytic action not only with ultraviolet light but also with visible light. With this configuration, simply leaving the adhesive interlining under visible light will cause the photocatalytic action to break down dirt adhering to the adhesive resin part. Also, with this configuration, dirt adhering to the adhesive interlining at 0.01 g / m 2 ~1.30g / m 2 Since the visible light responsive photocatalyst is added to the resin, the resin constituting the adhesive resin part has good decomposition performance against dirt while maintaining adhesion performance to the outer material. This prevents dirt from accumulating in the resin constituting the adhesive resin part. As a result, it is possible to prevent stains that occur over time from becoming noticeable.
[0009] In the adhesive interlining according to one aspect of the present invention, the visible light responsive photocatalyst may be titanium oxide containing 0.01% by mass to 2.0% by mass of a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver relative to the total amount of the visible light responsive photocatalyst (i.e., the total amount of the cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver and titanium oxide), or may be tungsten oxide containing 0.01% by mass to 2.0% by mass of a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver relative to the total amount of the visible light responsive photocatalyst. With this configuration, the visible light responsive photocatalyst can be easily prepared and dirt attached to the adhesive resin part can be decomposed. In addition, titanium oxide and tungsten oxide that do not contain at least one of the promoters platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver do not qualify as visible light responsive photocatalysts.
[0010] In the adhesive interlining according to one aspect of the present invention, the adhesive resin part may have dot points of 20 / 25.4 mm to 45 / 25.4 mm. With this configuration, good adhesion performance to the outer fabric can be ensured and dirt on the outer fabric with which the adhesive resin part comes into contact can also be dissolved.
[0011] In the adhesive interlining according to one aspect of the present invention, the base fabric may be subjected to a stain-resistant treatment. In this configuration, adhesion of stains to the base fabric of the adhesive interlining can be suppressed.
[0012] In the adhesive interlining according to one aspect of the present invention, the base fabric may be formed to contain polyester false twist yarn. In this configuration, dirt is less likely to adhere to the base fabric, and dirt that does adhere can be easily removed.
[0013] A clothing fabric according to one aspect of the present invention comprises the above-mentioned adhesive interlining and a surface fabric attached to the adhesive interlining via an adhesive resin part. With this configuration, the stains on the clothing fabric are decomposed by photocatalysis simply by leaving the stains under visible light. This prevents the stains from accumulating in the resin that constitutes the adhesive resin part. As a result, the stains that develop over time can be prevented from becoming noticeable.
[0014] In the clothing fabric according to one aspect of the present invention, the outer fabric may be subjected to a hydrophilic stain-resistant treatment, and the base fabric may be subjected to a water- and oil-repellent stain-resistant treatment. In this configuration, it is possible to effectively prevent stains from adhering to the outer fabric portion of the clothing fabric and the base fabric portion of the adhesive interlining, and the clothing has an excellent wearing feel. Here, the outer fabric (or base fabric) subjected to a hydrophilic stain-resistant treatment refers to an outer fabric (or base fabric) having a stain-resistant evaluation of grade 2 or higher for the outer fabric (or base fabric) alone based on the JIS L 1919 B method. The base fabric (or outer fabric) subjected to a water- and oil-repellent stain-resistant treatment refers to an outer fabric (or outer fabric) having a stain-resistant evaluation of grade 2-3 or higher for the base fabric (or fabric) alone based on the JIS L 1919 C method. Here, an example of the hydrophilic stain-resistant treatment is SR (Soil Release) treatment, and an example of the water- and oil-repellent stain-resistant treatment is SG (Soil Guard) treatment. Effect of the Invention
[0015] According to one aspect of the present invention, it is possible to suppress the visibility of stains that occur over time. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view showing an adhesive interlining according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a clothing fabric including an adhesive interlining for clothing according to one embodiment. [Diagram 3] The table in FIG. 3 lists the details and evaluation results of Examples 1 to 4 and Comparative Examples 1 to 4. [Figure 4]The table in FIG. 4 lists the details and evaluation results of Examples 5 to 7 and Comparative Examples 5 to 7. [Diagram 5] The table in FIG. 5 lists the details and evaluation results of Examples 8 to 15. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an adhesive interlining 1 according to one embodiment will be described with reference to the drawings. In the description of the drawings, the same elements are given the same reference numerals, and duplicated descriptions will be omitted. The dimensional ratios of the drawings do not necessarily match those in the description.
[0018] As shown in FIG. 1, the adhesive interlining 1 includes a base fabric 10 and an adhesive resin portion 20 fixed to a first surface 10A of the base fabric 10.
[0019] The base fabric 10 is a woven or knitted fabric, and in the case of a woven fabric, for example, it is a fabric woven using warp and weft yarns. The warp and weft yarns of the base fabric 10 may be made of crimped yarns. Examples of crimped yarns include false twist textured yarns. False twist textured yarns are textured yarns processed with a false twisting machine. False twist textured yarns are the mainstream of crimp textured yarns, and are also called false twist yarns. The fineness of the warp and weft yarns is, for example, 10 dtex to 333 dtex, preferably 15 dtex to 167 dtex, more preferably 20 dtex to 111 dtex, even more preferably 25 dtex to 80 dtex, particularly preferably 27 dtex to 60 dtex, and most preferably 30 dtex to 50 dtex.
[0020] The base fabric 10 may be of any material or structure as long as it has the necessary strength as an adhesive interlining. Examples of materials include natural fibers such as cotton, linen, silk, and wool, regenerated fibers such as rayon and cupra, semi-synthetic fibers such as acetate and triacetate, and synthetic fibers such as nylon, polyester, acrylic, urethane, polypropylene, polyethylene, and polyvinyl chloride, and preferably nylon fiber, polyester fiber, or acrylic fiber filament. Examples of fabric structures include woven fabrics (plain weave, twill weave, satin weave, etc.) and knitted fabrics made from the above materials.
[0021] The warp weave density (vertical density) of the base fabric 10 is, for example, 60 / 25.4mm to 140 / 25.4mm, preferably 80 / 25.4mm to 120 / 25.4mm, and more preferably 90 / 25.4mm to 110 / 25.4mm. The weft weave density (horizontal density) of the base fabric 10 is, for example, 20 / 25.4mm to 100 / 25.4mm, preferably 40 / 25.4mm to 80 / 25.4mm, and more preferably 50 / 25.4mm to 70 / 25.4mm. The ratio of the weft weave density to the warp weave density (weft weave density / warp weave density) is, for example, in the range of 0.3 to 0.9, preferably in the range of 0.4 to 0.8, and more preferably in the range of 0.5 to 0.7.
[0022] The warp and weft yarns constituting the base fabric 10 preferably contain multifilament yarn, more preferably polyester multifilament yarn, and even more preferably polyester false twist yarn, since this makes it difficult for dirt to adhere to the base fabric and makes it easier to remove any dirt that does adhere.
[0023] The base fabric 10 is subjected to a stain-resistant treatment. Specifically, the first surface 10A and the second surface 10B of the base fabric 10 are subjected to a stain-resistant treatment. Examples of stain-resistant treatment include hydrophilic stain-resistant treatment and water- and oil-repellent stain-resistant treatment. An example of the hydrophilic stain-resistant treatment is SR treatment. SR treatment is a known treatment that hydrophilizes the surface of the hydrophobic base fabric 10 to make it easier to remove stains by washing or the like. An example of the water- and oil-repellent stain-resistant treatment is SG treatment. SG treatment is a known treatment that imparts water- and oil-repellent properties to the base fabric 10 by processing it with, for example, a fluorine-based resin, making it difficult for hydrophilic and oil-philic stains to adhere. The base fabric 10 of this embodiment is subjected to SG treatment. Since stains are more difficult to adhere to the clothing fabric, it is preferable that the base fabric 10 is subjected to a water- and oil-repellent stain-resistant treatment. On the other hand, from the viewpoint of comfort when used as a clothing fabric, it is preferable that the base fabric 10 is subjected to a hydrophilic stain-resistant treatment.
[0024] The adhesive resin part 20 is formed from resin R1. The resin R1 is a thermoplastic resin, usually called a hot melt resin, which is plasticized by heat and exhibits adhesive ability after cooling. The adhesive resin part 20 is formed in a circular shape in a plan view. As shown in FIG. 2, the adhesive resin part 20 is provided to bond the adhesive interlining 1 to the outer fabric 70. The adhesive resin part 20 is formed by transferring the resin R1 to the first surface 10A of the base fabric 10 by a gravure roll or the like, and heating it to fix a part of it to the first surface 10A of the base fabric 10.
[0025] Examples of the resin R1 include polyamide, polyurethane, polyester, polypropylene, polyethylene, and modified ethylene vinyl acetate copolymer. The resin R1 may contain at least one of a polymerization initiator, a crosslinking agent, a pigment, a dye, a drying inhibitor, and other modifiers, as necessary. The melting point of the resin R1 is 90°C to 150°C, preferably 105°C to 125°C.
[0026] The adhesive resin portion 20 is formed in a dot shape. The adhesive resin portion 20 is attached to the first surface 10A, which is one surface of the base fabric 10, by the adhesiveness of the resin R1 forming the adhesive resin portion 20. Note that the "dot shape" usually means that a plurality of circular dots are regularly arranged, but the shape or arrangement of each dot is not particularly limited. For example, the shape of each dot may be a square, hexagon, star, or the like. Also, each dot may be irregularly arranged.
[0027] The size (dot diameter) of the adhesive resin portion 20 is, for example, 80 μm to 1000 μm, preferably 100 μm to 800 μm, and more preferably 150 μm to 500 μm.
[0028] The number (points) of adhesive resin parts 20 is 20 pieces / 25.4 mm to 45 pieces / 25.4 mm, preferably 23 pieces / 25.4 mm to 44 pieces / 25.4 mm, more preferably 27 pieces / 25.4 mm to 43 pieces / 25.4 mm, even more preferably 28 pieces / 25.4 mm to 42 pieces / 25.4 mm, particularly preferably 29 pieces / 25.4 mm to 41 pieces / 25.4 mm, and most preferably 30 pieces / 25.4 mm to 40 pieces / 25.4 mm.
[0029] The area occupancy rate of the adhesive resin part 20 relative to the base fabric 10 is 0.1% to 30.0%, preferably 0.5% to 20.0%, more preferably 1.0% to 15.0%, even more preferably 2.0 to 10.0%, particularly preferably 3.0 to 9.0%, and most preferably 4.0 to 8.0%.
[0030] A visible light responsive photocatalyst R2 is added to the resin R1 of this embodiment. An example of the visible light responsive photocatalyst R2 is titanium oxide containing 0.01% by mass to 2.0% by mass of a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver, based on the total amount of the visible light responsive photocatalyst R2. Another example of the visible light responsive photocatalyst R2 is tungsten oxide containing 0.01% by mass to 2.0% by mass of a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver, based on the total amount of the visible light responsive photocatalyst R2. The visible light responsive photocatalyst R2 is preferably titanium oxide containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver as a promoter in an amount of 0.01% by mass to 2.0% by mass relative to the total amount of the visible light responsive photocatalyst R2, more preferably titanium oxide containing copper oxide or iron oxide as a promoter in an amount of 0.01% by mass to 2.0% by mass relative to the total amount of the visible light responsive photocatalyst R2, and even more preferably titanium oxide containing copper oxide as a promoter in an amount of 0.01% by mass to 2.0% by mass relative to the total amount of the visible light responsive photocatalyst R2. The ratio of the amount of the promoter to the total amount of the visible light responsive photocatalyst R2 is preferably 0.1% by mass to 1.8% by mass, and more preferably 0.5% by mass to 1.5% by mass. If the content of the promoter to the total amount of the visible light responsive photocatalyst R2 is less than 0.01% by mass, the function of decomposing dirt under visible light may be insufficient. On the other hand, if the content of the promoter with respect to the total amount of the visible light responsive photocatalyst R2 exceeds 2.0 mass %, it may be disadvantageous from the viewpoint of economy.
[0031] The visible light responsive photocatalyst R2 has a function of decomposing dirt. Therefore, the adhesive interlining 1 of this embodiment has a function of decomposing dirt attached to the adhesive resin part 20. The amount of the visible light responsive photocatalyst R2 contained in the resin R1 is 0.01 g / m 2 ~1.30g / m 2 and preferably 0.05 g / m 2 ~1.10g / m 2 and more preferably 0.10 g / m2 ~0.90g / m 2 and more preferably 0.20 g / m 2 ~0.80g / m 2 and particularly preferably 0.45 g / m 2 ~0.75g / m 2 The amount of visible light responsive photocatalyst R2 is 0.45 g / m 2 In the above cases, dirt on the clothing fabric is particularly easily removed. The amount of the visible light responsive photocatalyst R2 can be measured by ICP-MS. The ratio of the amount of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, or silver to the amount of titanium oxide or tungsten oxide can be measured by ICP-MS.
[0032] The amount of resin R1 in this embodiment is 1 g / m 2 ~30g / m 2 and preferably 3 g / m 2 ~25g / m 2 The ratio of the visible light responsive photocatalyst R2 to the total amount of the resin R1 and the visible light responsive photocatalyst R2 is 0.04% by mass to 10.0% by mass, preferably 0.1% by mass to 8.0% by mass, more preferably 0.3% by mass to 5.0% by mass, and particularly preferably 0.5% by mass to 4.0% by mass. When the ratio of the visible light responsive photocatalyst R2 to the total amount of the resin R1 and the visible light responsive photocatalyst R2 is less than 0.04% by mass, it is difficult to achieve both the texture of the base fabric and the dirt resistance and dirt removal properties of the base fabric. On the other hand, when the ratio of the visible light responsive photocatalyst R2 to the total amount of the resin R1 and the visible light responsive photocatalyst R2 exceeds 10.0% by mass, the adhesive performance of the adhesive interlining 1 decreases.
[0033] Next, a description will be given of a method for producing the adhesive interlining 1 of the above embodiment. The method for producing the adhesive interlining 1 of the present embodiment includes a preparation step, an impregnation step, an attachment step, and a stain-proofing treatment step.
[0034] In the preparation step, the base fabric 10, the resin R1 constituting the adhesive resin part 20 to be attached to the first surface 10A of the base fabric 10, and the visible light responsive photocatalyst R2 to be contained in the resin R1 are prepared. As the visible light responsive photocatalyst R2, for example, titanium oxide containing a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver in an amount of 0.01 mass % to 2.0 mass % relative to the total amount of the visible light responsive photocatalyst R2 is prepared, or tungsten oxide containing a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver in an amount of 0.01 mass % to 2.0 mass % relative to the total amount of the visible light responsive photocatalyst R2 is prepared. In the containing step, the amount of the visible light responsive photocatalyst R2 contained in the resin R1 is, for example, 0.01 g / m 2 ~1.30g / m 2 The resin R1 contains a visible light responsive photocatalyst R2 so that the above-mentioned condition is satisfied.
[0035] In the adhering step, the resin R1 containing the visible light responsive photocatalyst R2 prepared in the containing step is adhered to the first surface 10A of the base fabric 10 to form the adhesive resin part 20. In this embodiment, the adhering step is performed by gravure transfer. The adhering step can also be performed by using screen printing, letterpress printing, intaglio printing, lithographic printing, inkjet, a dispenser, a spray, or the like.
[0036] Next, a clothing fabric 50 including the adhesive interlining 1 according to one embodiment will be described. As shown in Fig. 2, the clothing fabric 50 includes the above-mentioned adhesive interlining 1 and an outer fabric 70. The outer fabric 70 is fixed via an adhesive resin part 20 provided on the first surface 10A of the base fabric 10.
[0037] The outer fabric 70 may be made of any material or structure as long as it has the necessary strength as a clothing fabric. Examples of materials include natural fibers such as cotton, linen, silk, and wool, regenerated fibers such as rayon and cupra, semi-synthetic fibers such as acetate and triacetate, nylon, polyester, acrylic, urethane, polypropylene, polyethylene, and polyvinyl chloride.
[0038] The outer fabric 70 is subjected to a stain-resistant treatment. Specifically, the stain-resistant treatment is applied to both the first surface 70A and the second surface 70B of the outer fabric 70. Examples of stain-resistant treatment include hydrophilic stain-resistant treatment and water- and oil-repellent stain-resistant treatment. The outer fabric 70 of this embodiment is subjected to SR treatment (hydrophilic stain-resistant treatment). From the viewpoint of making it more difficult for stains to adhere to the clothing fabric and making it easier to remove stains during washing, it is preferable that the outer fabric 70 is subjected to a water- and oil-repellent stain-resistant treatment. On the other hand, from the viewpoint of the wearing comfort as a clothing fabric, it is preferable that the outer fabric 70 is subjected to a hydrophilic stain-resistant treatment.
[0039] From the viewpoint that the base fabric and the cloth make it difficult for dirt to adhere and dirt can be removed more easily, it is preferable that the base fabric 10 and the outer fabric 70 are treated with a water- and oil-repellent stain-resistant treatment. On the other hand, from the viewpoint of achieving both a high level of ease of removing dirt and a comfortable fit, it is preferable that the base fabric 10 is treated with a water- and oil-repellent stain-resistant treatment and the outer fabric 70 is treated with a hydrophilic stain-resistant treatment.
[0040] In the clothing fabric 50 having the adhesive interlining 1 according to the embodiment described above, dirt adhering to the adhesive resin portion 20 is decomposed by photocatalysis simply by leaving the clothing fabric 50 under visible light. 2 ~1.30g / m 2 Since the visible light responsive photocatalyst R2 is added to the resin R1, it is possible to maintain adhesion to the outer material 70 while having the ability to decompose dirt adhering to the adhesive resin part 20. This prevents dirt from accumulating in the resin R1 constituting the adhesive resin part 20. As a result, it is possible to prevent stains that occur over time from becoming noticeable.
[0041] As the visible light responsive photocatalyst R2 of the adhesive interlining 1 included in the clothing fabric 50 of the above embodiment, titanium oxide containing 0.01 mass% to 2.0 mass% of a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver relative to the total amount of the visible light responsive photocatalyst R2 is adopted, or tungsten oxide containing 0.01 mass% to 2.0 mass% of a cocatalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver relative to the total amount of the visible light responsive photocatalyst R2 is adopted. This makes it possible to easily prepare the visible light responsive photocatalyst R2 and to decompose dirt attached to the adhesive resin part 20.
[0042] The adhesive interlining 1 included in the clothing fabric 50 of the above embodiment has 20 dot points / 25.4 mm to 45 dot points / 25.4 mm in the adhesive resin part 20. This ensures good adhesion to the outer fabric 70 and also ensures a sufficient contact area of the adhesive resin part 20 with the outer fabric 70. As a result, a new effect can be achieved in that dirt on the outer fabric 70 that the adhesive resin part 20 comes into contact with can also be dissolved.
[0043] The base fabric 10 of the adhesive interlining 1 included in the clothing fabric 50 of the above embodiment is subjected to a stain-resistant treatment. This makes it possible to prevent the base fabric 10 of the adhesive interlining 1 from becoming stained.
[0044] In the adhesive interlining 1 included in the clothing fabric 50 of the above embodiment, the base fabric 10 is formed containing polyester false twisted yarn. This makes it difficult for dirt to adhere to the base fabric 10, and makes it easier to remove any dirt that does adhere.
[0045] In the clothing fabric 50 of the above embodiment, the outer fabric 70 is treated with a hydrophilic stain-resistant treatment, and the base fabric 10 is treated with a water- and oil-repellent stain-resistant treatment. This effectively prevents the outer fabric 70 of the clothing fabric 50 and the base fabric 10 of the adhesive interlining 1 from becoming soiled, and provides an excellent wearing feel as clothing. Generally, the texture of the fabric deteriorates when treated with a water- and oil-repellent stain-resistant treatment, but the base fabric 10 of the adhesive interlining 1, which is treated with a water- and oil-repellent stain-resistant treatment, does not come into contact with the human body. This effectively prevents the fabric from becoming soiled without impairing the wearer's comfort.
[0046] Next, the resin R1 forming the adhesive resin portion 20 is 0.01 g / m 2 ~1.30g / m 2 The fact that the inclusion of the visible light responsive photocatalyst R2 can suppress the conspicuousness of stains that develop over time will be described with reference to Examples 1 to 15 and Comparative Examples 1 to 7 shown below. Note that the adhesive interlining 1 according to one aspect of the present invention and the clothing fabric 50 including the same are not limited to those produced according to Examples 1 to 15 shown below.
[0047] The resin R1, visible light responsive photocatalyst R2, and non-visible light responsive photocatalyst used in Examples 1 to 15 and Comparative Examples 1 to 7 are as follows. Resin R1 (PA): MSChemie Japan 2AP1 (copolymer nylon, melting point 110°C) Visible light responsive photocatalyst R2: DIC Corporation HPS POWDER AC-20 (titanium oxide containing copper oxide: the copper oxide content of the total amount of titanium oxide and copper oxide is 1.0% (mass%)) Invisible light responsive photocatalyst: Nacalai Tesque, Inc. Titanium oxide (athanase type) The outer fabric 70 used in Examples 1 to 15 and Comparative Examples 1 to 7 is as follows. Outer fabric 70: TC broadcloth (plain weave fabric woven with 45-count spun yarn of 65% polyester and 35% cotton (vertical density 88 threads / 25.4 mm, horizontal density 64 threads / 25.4 mm))
[0048] Example 1 As shown in FIG. 1, a fabric consisting of a 30 dtex warp yarn and a 30 dtex weft yarn made of polyester false twist textured yarn (T100) was prepared as the base fabric 10 used in Example 1. The density of the base fabric 10 is 100 weft yarns / 25.4 mm and 60 warp yarns / 25.4 mm. Then, a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 10 so as to have the following characteristics to form an adhesive interlining 1. Then, a surface fabric 70 was attached to the adhesive interlining 1 by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to prepare a clothing fabric 50 of Example 1. The presence or absence of a stain-resistant treatment of the base fabric 10 and the surface fabric 70 is as shown below.
[0049] Resin amount of resin R1: 5g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.15 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0050] Example 2 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, forming an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 2. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0051] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0052] Example 3 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 3. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0053] Resin amount of resin R1: 20g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.60 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0054] Example 4 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 4. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0055] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 17 pieces / 25.4mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0056] Comparative Example 1 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a non-visible light responsive photocatalyst of the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 1. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0057] Resin amount of resin R1: 5g / m 2 Content of non-visible light responsive photocatalyst in resin R1: 3.00% by mass Content of invisible light responsive photocatalyst in resin R1: 0.15g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in non-visible light responsive photocatalyst: None Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0058] Comparative Example 2 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 2. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0059] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 0.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.00 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0060] Comparative Example 3 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 3. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0061] Resin amount of resin R1: 5g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 0.01% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.0005 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0062] Comparative Example 4 A base fabric 10 of the same composition as in Example 1 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 4. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0063] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 20.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 2.00 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0064] For each of the clothing fabrics 50 of Examples 1 to 4 and Comparative Examples 1 to 4, (A) stain evaluation immediately after washing, (B) stain evaluation 4 weeks after washing, and (C) physical properties (adhesion performance) were evaluated by the following methods.
[0065] (A) Soil evaluation immediately after washing The stain evaluation was based on the values measured according to Method C (drop wiping method) of the stain resistance test method for textile products in JIS L 1919. The stain components used in this test are as shown in Table 1 below. [Table 1]
[0066] Next, the above-mentioned soiling components were dropped onto the clothing fabrics 50 of Examples 1 to 4 and Comparative Examples 1 to 4 from the outer fabric 70 side, and a washing process was performed according to the JIS L 1930 C4M method. The clothing fabrics 50 were left to stand under a 100 W fluorescent lamp, and immediately thereafter, the soiling grade was determined. The soiling grade was determined using the staining gray scale defined in JIS L 0805.
[0067] (B) Soil evaluation 4 weeks after washing The stain components described in (A) Evaluation of stains immediately after washing were dropped onto the outer fabric 70 side of each of the clothing fabrics 50 of Examples 1 to 4 and Comparative Examples 1 to 4, and the clothing fabrics 50 were washed according to the JIS L1930 C4M method. The clothing fabrics 50 were left standing under a 100W fluorescent lamp for 4 weeks, after which the stain grade was determined by the above method.
[0068] (C) Physical property evaluation For each of the clothing fabrics 50 of Examples 1 to 4 and Comparative Examples 1 to 4, an evaluation was carried out regarding the adhesive performance between the base fabric 10 and the outer fabric 70. In detail, each clothing fabric 50 was subjected to a washing treatment in accordance with the JIS L 1930 C4M method, and a test was carried out in accordance with the method for measuring the peel strength of adhesive interlinings specified in JIS L 1086 Testing methods for adhesive interlinings and adhesive fabrics.
[0069] The results of evaluation of the clothing fabrics 50 of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in the table of Figure 3. The numerical values in (A) the stain evaluation immediately after washing and (B) the stain evaluation 4 weeks after washing shown in the table of Figure 3 indicate the stain grade. The stain grade was determined using the stain gray scale defined in JIS L 0805, and the higher the numerical value, the smaller the difference between the stained and non-stained areas. The details of the symbols in (C) the physical property evaluation are as follows: ◎: The adhesive strength measured by the above peel strength measurement method is 300 (gf / 25.4 mm) or more and no partial peeling is observed. ×: The adhesive strength measured by the above peel strength measurement method is less than 300 (gf / 25.4 mm), or partial peeling is observed.
[0070] In the clothing fabrics 50 of Examples 1 to 4, the stain evaluation four weeks after the washing treatment was improved compared to the stain evaluation immediately after the washing treatment, and good results were also obtained in the physical property evaluation. 2 ~1.30g / m 2 It was confirmed that the clothing fabrics 50 of Examples 1 to 4, to which the visible light responsive photocatalyst R2 was added, had the effect of decomposing dirt over time and could maintain adhesion performance. On the other hand, the clothing fabric 50 of Comparative Example 1 had no difference in the stain evaluation between 4 weeks after washing and immediately after washing. In other words, it was confirmed that the clothing fabric 50 of Comparative Example 1, to which the invisible light responsive photocatalyst, which does not contain copper oxide as a promoter, was added, did not have the effect of decomposing dirt over time.
[0071] In addition, for the clothing fabrics 50 of Comparative Examples 2 and 3, the evaluation of stains did not change between immediately after the washing treatment and four weeks after the washing treatment. 2 It was confirmed that the clothing fabrics 50 of Comparative Examples 2 and 3, in which less than 1.30 g / m of visible light responsive photocatalyst R2 was added, did not have the effect of decomposing dirt over time. Also, in the clothing fabric 50 of Comparative Example 4, the stain evaluation 4 weeks after washing was improved compared to the stain evaluation immediately after washing, but good results were not obtained in the physical property evaluation. 2 It was confirmed that the clothing fabric 50 of Comparative Example 4, to which a larger amount of visible light responsive photocatalyst R2 was added, was unable to maintain its adhesive performance.
[0072] Example 5 As shown in the table of FIG. 4, a fabric consisting of a warp yarn of 45 count (131 dtex) and a weft yarn of 45 count (131 dtex) made of polyester / cotton blended yarn (mixing ratio: T / C=65 / 35) was prepared as the base fabric 10 used in Example 5. The density of the base fabric 10 is 100 threads / 25.4 mm for the weft and 60 threads / 25.4 mm for the warp. Then, the resin R1 containing the visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 10 so as to have the following characteristics to form an adhesive interlining 1. Then, the outer fabric 70 was attached to the adhesive interlining 1 by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to prepare the clothing fabric 50 of Example 5. The presence or absence of antifouling treatment of the base fabric 10 and the outer fabric 70 is as shown below.
[0073] Resin amount of resin R1: 5g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.15 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0074] Example 6 A base fabric 10 of the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 6. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0075] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0076] Example 7 A base fabric 10 of the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 7. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0077] Resin amount of resin R1: 20g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.60 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0078] Comparative Example 5 A base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 5. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0079] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 0.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.00 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0080] Comparative Example 6 A base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 6. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0081] Resin amount of resin R1: 5g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 0.01% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.0005 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0082] Comparative Example 7 A base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Comparative Example 7. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0083] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 20.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 2.00 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Surface 70 stain-resistant treatment: Untreated
[0084] In the clothing fabrics 50 of Examples 5 to 7, the stain evaluation four weeks after the washing treatment was improved compared to the stain evaluation immediately after the washing treatment, and good results were also obtained in the physical property evaluation. 2 ~1.30g / m 2 It was confirmed that the clothing fabrics 50 of Examples 5 to 7 to which the visible light responsive photocatalyst R2 was added had the effect of decomposing stains over time and also maintained their adhesive performance.
[0085] On the other hand, for the clothing fabrics 50 of Comparative Examples 5 and 6, the evaluation of stains four weeks after the washing treatment did not change from the evaluation of stains immediately after the washing treatment. 2It was confirmed that the clothing fabrics 50 of Comparative Examples 5 and 6, in which less than 1.30 g / m of visible light responsive photocatalyst R2 was added, did not have the effect of decomposing dirt over time. Also, in the clothing fabric 50 of Comparative Example 7, the stain evaluation 4 weeks after washing was improved compared to the stain evaluation immediately after washing, but good results were not obtained in the physical property evaluation. 2 It was confirmed that the clothing fabric 50 of Comparative Example 7, to which a larger amount of visible light responsive photocatalyst R2 was added, was unable to maintain its adhesive performance.
[0086] Next, the effects of the stain-proofing treatment of the base fabric 10 and the outer fabric 70 were verified in Examples 8 to 15.
[0087] Example 8 5, a base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 8. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0088] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Soil-resistant treatment of base fabric 10: SR treatment (hydrophilic stain-resistant treatment; soil-resistant evaluation grade 2 based on JIS L 1919 B method for base fabric alone) Surface 70 stain-resistant treatment: Untreated
[0089] Example 9 A base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 9. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0090] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Soil-resistant treatment of base fabric 10: SG treatment (water- and oil-repellent stain-resistant treatment; soil-resistant evaluation grade 4 based on JIS L 1919 C method for base fabric alone) Surface 70 stain-resistant treatment: Untreated
[0091] Example 10 A base fabric 10 of the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 10. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0092] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Stain-resistant treatment for outer fabric 70: SR treatment (hydrophilic stain-resistant treatment; stain-resistant rating of the outer fabric alone based on JIS L 1919 B method, Class 2)
[0093] Example 11 A base fabric 10 of the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 11. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0094] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: Untreated Stain-resistant treatment for outer fabric 70: SG treatment (water- and oil-repellent stain-resistant treatment; stain-resistant rating of outer fabric alone based on JIS L 1919 C method, grade 4)
[0095] Example 12 A base fabric 10 of the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 12. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0096] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Stain-resistant treatment of base fabric 10: SR treatment (hydrophilic stain-resistant treatment; stain-resistant evaluation grade 2 based on JIS L 1919 B method for interlining alone) Stain-resistant treatment for outer fabric 70: SR treatment (hydrophilic stain-resistant treatment; stain-resistant rating of the outer fabric alone based on JIS L 1919 B method, Class 2)
[0097] (Example 13) A base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 13. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0098] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Soil-resistant treatment of base fabric 10: SG treatment (water- and oil-repellent stain-resistant treatment; soil-resistant evaluation grade 4 based on JIS L 1919 C method for base fabric alone) Stain-resistant treatment for outer fabric 70: SR treatment (hydrophilic stain-resistant treatment; stain-resistant rating of the outer fabric alone based on JIS L 1919 B method, Class 2)
[0099] Example 14 A base fabric 10 of the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 of the above composition was attached to the base fabric 1 so as to have the following characteristics, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 14. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0100] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Soil-resistant treatment of base fabric 10: SR treatment (hydrophilic stain-resistant treatment; soil-resistant evaluation grade 2 based on JIS L 1919 B method for base fabric alone) Stain-resistant treatment for outer fabric 70: SG treatment (water- and oil-repellent stain-resistant treatment; stain-resistant rating of outer fabric alone based on JIS L 1919 C method, grade 4)
[0101] Example 15 A base fabric 10 having the same composition as in Example 5 was prepared, and a resin R1 containing a visible light responsive photocatalyst R2 having the above composition was attached to the base fabric 1 so as to have the following characteristics to form an adhesive interlining 1, and then a surface fabric 70 was attached by a heat adhesion treatment (130°C x 10 seconds x 3.0 kgf / cm) to produce a clothing fabric 50 of Example 15. The presence or absence of a stain-resistant treatment for the base fabric 10 and the surface fabric 70 is as shown below.
[0102] Resin amount of resin R1: 10g / m 2 Content of visible light responsive photocatalyst R2 relative to resin R1: 3.00% by mass Content of visible light responsive photocatalyst R2 relative to resin R1: 0.30 g / m 2 Adhesive resin part 20 points: 40 pieces / 25.4 mm Presence or absence of co-catalyst in visible light responsive photocatalyst R2: Yes (Contains 1.0% by mass of copper oxide as a promoter relative to the total amount of visible light responsive photocatalyst R2) Soil-resistant treatment of base fabric 10: SG treatment (water- and oil-repellent stain-resistant treatment; soil-resistant evaluation grade 4 based on JIS L 1919 C method for base fabric alone) Stain-resistant treatment for outer fabric 70: SG treatment (water- and oil-repellent stain-resistant treatment; stain-resistant rating of outer fabric alone based on JIS L 1919 C method, grade 4)
[0103] In the clothing fabrics 50 of Examples 8 to 15, in which at least one of the base fabric 10 and the outer fabric 70 was subjected to a stain-resistant treatment, SG treatment or SR treatment, the stain evaluation immediately after washing was improved compared to the clothing fabrics 50 of Examples 5 to 7, in which the base fabric 10 and the outer fabric were not subjected to a stain-resistant treatment. That is, it was confirmed that the clothing fabrics 50 of Examples 8 to 15 were able to suppress the adhesion of stains. Furthermore, in the clothing fabrics 50 of Examples 8 to 15, the stain evaluation 4 weeks after washing was improved compared to the stain evaluation immediately after washing, and good results were also obtained in the physical property evaluation. That is, in the clothing fabrics 50 of Examples 8 to 15, the stain evaluation 4 weeks after washing was improved compared to the stain evaluation immediately after washing, and good results were also obtained in the physical property evaluation. That is, 2 ~1.30g / m 2 It was confirmed that the clothing fabrics 50 of Examples 8 to 15, to which the visible light responsive photocatalyst R2 was added, had the effect of decomposing stains over time and also maintained their adhesive performance.
[0104] In addition, the clothing fabrics 50 of Examples 8 to 15 were evaluated for (D) wearing comfort. In detail, shirts were made using the clothing fabrics 50 of Examples 8 to 15 for the collar and collar stand, and a monitor test was conducted by 10 people to evaluate the wearing comfort of the shirts. The wearing comfort was evaluated comprehensively based on the clinging to the skin when worn and sweat absorption, etc., and shirts that were evaluated as having no discomfort by 8 or more out of 10 people were evaluated as "◎", shirts that were evaluated as having no discomfort by 5 to 8 people but not yet 8 people were evaluated as "◯", and shirts that were evaluated as having no discomfort by less than 5 people were evaluated as "×". The evaluation results of the wearing comfort of the shirts using the clothing fabrics 50 of Examples 8 to 15 for the collar and collar stand are shown in the (D) Wearing Comfort Evaluation column in the chart of FIG. 5.
[0105] Although one embodiment and Examples 1 to 15 have been described above, one aspect of the present invention is not limited to the above embodiment and examples, and various modifications are possible without departing from the spirit of the invention.
[0106] In the adhesive interlining 1 of the above embodiment, an example has been described in which the adhesive resin part 20 made of the resin R1 containing the visible light responsive photocatalyst R2 is disposed on the first surface 10A, which is one surface of the base fabric 10, but one aspect of the present invention is not limited to this. The adhesive resin part 20 made of the resin R1 containing the visible light responsive photocatalyst R2 may be disposed on both surfaces of the base fabric 10, the first surface 10A and the second surface 10B. [Explanation of symbols]
[0107] 1... adhesive interlining, 10... base fabric, 20... adhesive resin part, 50... clothing fabric, 70... outer fabric, R1... resin, R2... visible light responsive photocatalyst.
Claims
1. A base fabric; and an adhesive resin portion made of polyamide of 5 g / m 2 to 20 g / m 2 provided in a dot pattern on one surface of the base fabric, The polyamide has a viscosity of 0.01 g / m 2 ~1.30g / m 2 a visible light responsive photocatalyst is added, and the ratio of the visible light responsive photocatalyst to the total amount of the polyamide and the visible light responsive photocatalyst is 0.04% by mass to 10.0% by mass; The adhesive interlining has dot points of 29 / 25.4 mm to 45 / 25.4 mm.
2. The visible light responsive photocatalyst is Titanium oxide containing 0.01% by mass to 2.0% by mass of a co-catalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver, based on the total amount of the visible light responsive photocatalyst; Or, 2. The adhesive interlining according to claim 1, which is a tungsten oxide containing 0.01% by mass to 2.0% by mass of a co-catalyst containing at least one of platinum, copper oxide, iron oxide, palladium, rhodium, ruthenium, nickel, magnesium, gold, and silver, based on the total amount of the visible light responsive photocatalyst.
3. 3. The adhesive interlining according to claim 1, wherein the base fabric is treated to be stain resistant.
4. The adhesive interlining according to any one of claims 1 to 3, wherein the base fabric is formed by containing polyester false twist textured yarn.
5. The adhesive interlining according to any one of claims 1 to 4, A surface fabric is attached to the adhesive interfacing via the adhesive resin portion.
6. 6. The fabric for clothing according to claim 5, wherein the outer fabric is treated to be hydrophilic and stain-resistant, and the base fabric is treated to be water-, oil-, and stain-resistant.
Citation Information
Patent Citations
Fiber structure
JP1999100771A
Submaterial
JP2001248064A
Soil resistant finish method for collar and cuff of shirt or blouse
JP2003213509A
Fibrous structure
JP2004183107A
Soil-resistant fiber structure having core substrate
JP2007237670A